Research on evaluation model of rock failure integrity under complex geological conditions in karst area - Jianbo, Ma; Zhongqi, Wang; En, Yang; Menghua, Liu (Frontiers in Earth Science, 2023)
The rich groundwater in karst areas will erode the rock structure, change the rock structure, and produce a large number of karst caves and soil caves. The geological conditions in the area are complex and diverse. How to conduct a good scientific assessment of the integrity of the rock after the project breaking in the complex karst environment poses a major test. Based on the area measurement method, numerical simulation and fitting experience in machine learning, an optimization model of rock fragmentation integrity is proposed in this paper. On the basis of the original model, combined with the field rock breaking test and simulation data, a correction factor is added to the design parameters of the xm prediction formula. Without changing the prediction accuracy of fine particles, this method will improve the prediction accuracy of large-scale blasting results. According to the comparison results of different rock failure integrity, the prediction accuracy of the optimized model is greatly improved. This study is of great significance to the evaluation of rock failure integrity and practical engineering applications.